(untitled) (Journal of Geography and Environmental Management, 2018)
Industrial centers are areas of greatest pollution of various media with heavy metals. Near large industrial centers, large number of heavy metals enter the soil, wherein soils of agrocenoses and cultivated crops can be polluted. A long period of self-cleaning of soils and the high cost of their artificial cleaning make mankind seek for new ways to solve the problem associated with the contamination of soils with heavy metals. The most promising direction in this area is the study of the genetic potential of plants and the identification of plant objects characterized by a minimum accumulation of heavy metals. The review presents data on the genotypic specificity of the adaptive potential of plants. Different types of plants have different biological characteristics that determine the availability of heavy metals. The flow of heavy metals into plants depends on the characteristics of the absorption of an element by different plant species. Soils characterized by a high polymetallic content of metals are distinguished by the formation of specific communities. Not only different species, but also varieties of one species differ in ability to accumulate ions of heavy metals, even with the same concentration in the soil. It is known that the ability to absorb, accumulate, and use chemical elements in plants is genetically determined. The physiological causes of the genotypic specificity of the absorption of elements of mineral nutrition by plants are ambiguous: they can be caused by differences, both in the primary mechanisms of ion uptake, and in their subsequent transport and metabolism. Researchers identify selectively important indicators of technologically resistant varieties: plasticity, duration of vegetation period, yield, size and selectivity of root systems, detoxification and localization of ecotoxicants in certain parts of the plant. An effective strategy to reduce yield losses is the use of varieties that have genes of tolerance or resistance to biotic and abiotic influences.